Citoprotective effect of camu-camu Myrciaria dubia on three celular lines of mouse exposed in vivo to potassium bromate - Rafael, Alvis (2010)
It was evaluated in vivo the cytoprotective capacity of the fruit of Myrciaria dubia H.B.K. MC VAUGH "Camu- camu (Myrtacea) against mutagenic damage caused by potassium bromate (68.5 mg/k) on three mouse cell lines (liver, kidney and blood cells). Mice (n = 120) were divided into three groups which drank ad libitum: distilled water; TI (negative control) and TIII (positive control), the TII group (positive control) drank the aque- ous extract (2 %) of the fruit of Camu-camu. After ten days, only the TII and TIII groups were intraperitoneally injected with a single dose of KBr03(68.5 mg/k). The camu-camu treatment lasted 35 days more, where they were euthanized to determine the frequency of DNA damage by means of the alkaline comet assay protocol. It was observed in all cell lines a cytoprotective effect of camu-camu (p<0.05) with respect with the negative control. The DNA-damaging effects of oxidative KBrO3 action is inhibited by the 2% aqueous extract of camu- camu fruit, probably by the presence of antioxidants such as ascorbic acid and flavonoids.